Research in Public Policy Analysis and ManagementResearch in Public Policy Analysis and Management (Vol 1), by Crecine John P. (Ed.). Greenwich, Conn.: JAI Press, Inc., 1981. 291 pp., $37.50. - Paul, Karen (Academy of Management Review, 1983)
This article presents a review of the book ?Research in Public Policy Analysis and Management,? vol. 1, by John P. Crecine.